2015
DOI: 10.1111/sms.12411
|View full text |Cite
|
Sign up to set email alerts
|

Exercise reverses OVA‐induced inhibition of glucocorticoid receptor and increases anti‐inflammatory cytokines in asthma

Abstract: The purpose of this study was to determine the effect of aerobic exercise training (AT) on the expression of glucocorticoid receptors (GR) and anti-inflammatory cytokines in an asthma model. BALB/c mice were divided into groups control (CT; nonsensitized/nontrained), aerobic training (AT; nonsensitized/trained), ovalbumin (OVA; sensitized/not trained), and OVA+AT (sensitized/trained). OVA groups received OVA by inhalation, and the AT groups completed 1, 3, or 7 days of exercise (60 min/session). Expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 56 publications
1
16
0
2
Order By: Relevance
“…Interestingly, in a pediatric asthma cohort, cells recovered from poor GC responders displayed lower GCR protein levels as compared with good GC responders (39). In this study, when the GCR level in lung homogenates was assessed using Western blot assays, we observed that repeated exposure of allergens on 2 or 4 consecutive d downregulated GCR expression in samples from A/J mice, in line with a previous report (40). Moreover, the reduction in lung tissue GCR protein levels was clearly impaired by dexamethasone given 1 h before provocation in the mice exposed to FIGURE 7.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, in a pediatric asthma cohort, cells recovered from poor GC responders displayed lower GCR protein levels as compared with good GC responders (39). In this study, when the GCR level in lung homogenates was assessed using Western blot assays, we observed that repeated exposure of allergens on 2 or 4 consecutive d downregulated GCR expression in samples from A/J mice, in line with a previous report (40). Moreover, the reduction in lung tissue GCR protein levels was clearly impaired by dexamethasone given 1 h before provocation in the mice exposed to FIGURE 7.…”
Section: Discussionsupporting
confidence: 91%
“…Potential mediating mechanisms include reductions in the serum T helper 2 proinflammatory cytokines interleukin (IL)-4, IL-5, and IL-6, IL-13-16, reductions in the monocyte chemoattractant protein 1 and keratinocyte chemoattractant protein (murine homologue to human IL-8), inhibition of nuclear factor kappa B (NFκB) activation, and increases in the anti-inflammatory cytokine IL-10, IL-1ra and circulating regulatory T cells. [84,[106][107][108][109]. Increased PADL was also associated with lower systemic inflammation (for every increase of 1000 steps per day, high sensitivity-CRP was reduced by 17%) in patients with severe asthma after adjustment for confounders, albeit no associations were found with measures of eosinophilic airway inflammation [31].…”
Section: Additional Mechanisms Of Benefitmentioning
confidence: 93%
“…In the absence of OPN, the exposure to allergen causes lesser lung fibroblast proliferation, reduced collagen deposition, diminished inflammatory cell accumulation, and decreased expression of VEGF, TGF-β and MMP-2 than is the case in OPN competent hosts [17]. Aerobic training in asthma reduces the levels of inflammatory mediators and proteins associated with the induction of airway remodeling, including OPN and VEGF, thus preserving airway integrity [159]. Within hours of infection with Mycobacterium tuberculosis, macrophages express genes involved in cell homing, including interleukin-8 and OPN.…”
Section: Immune and Inflammatory Conditionsmentioning
confidence: 94%